Harmonized System in Developing Countries - Carsten Weerth (Global Trade and Customs Journal, 2008)
More than 200 countries and economic regions worldwide are using the nomenclature of the Harmonized Commodity Description and Coding System (Harmonized System Convention: HS) and are basing their customs tariffs thereon. The number of HS headings (four-digit code) and HS subheadings (six-digit code) is altered every four to six years, when the nomenclature is revised and updated due to trade patterns and technical development (HS 1988, HS 1992, HS 1996, HS 2002, HS 2007). More gaps are emerging within the nomenclature and 34 headings will not be in use in the HS 2007 for the next four to six years. This article examines the application of the nomenclature within developing countries, since these are allowed to adopt older versions of the nomenclature.
Keywords: K33; K34; 330; Customs Law; World Customs Organization; Harmonized System; Nomenclature